(untitled) (MAUSAM, 2021)
This study has been carried out to find the groundwater quality of Burdwan district of West Bengal during pre-monsoon and post-monsoon. For this, the data of physicochemical parameters have been collected from Central Pollution Control Board (CPCB) website for the pre-monsoon and post-monsoon season for the year 2017. It is found that during the post-monsoon season, the water quality of all the stations falls in the category of excellent, and during the pre-monsoon season, the water quality of most of the stations is good.